The Palgrave Encyclopedia of Urban and Regional Futures 2022
DOI: 10.1007/978-3-030-51812-7_125-1
|View full text |Cite
|
Sign up to set email alerts
|

Circular Cities

Abstract: DefinitionCircular city is a concept inspired by biological metabolic systems that seeks to apply the principles and strategies of the circular economy at the different scales of urban functioning. By doing so, a circular city is meant to reduce the intake of primary resources and energy and resulting environmental impacts, such as waste and emissions. Its functioning is (re)defined by efforts aiming to close, narrow, and/or slow material and energy flows. A circular city is a normative concept, implying thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Like IS literature, CE research has started to investigate larger scales, explaining how CE can be implemented in cities and regions. This has led to an increased awareness of the importance of space in the circular transition, producing a new body of literature falling under the name of "circular cities" (Bucci Ancapi et al, 2022;Prendeville et al, 2018;. Literature on circular cities can be separated into three main perspectives: space, people, and flows.…”
Section: Tocmentioning
confidence: 99%
“…Like IS literature, CE research has started to investigate larger scales, explaining how CE can be implemented in cities and regions. This has led to an increased awareness of the importance of space in the circular transition, producing a new body of literature falling under the name of "circular cities" (Bucci Ancapi et al, 2022;Prendeville et al, 2018;. Literature on circular cities can be separated into three main perspectives: space, people, and flows.…”
Section: Tocmentioning
confidence: 99%
“…CE policies seek to intervene in the so-called linear metabolism of cities, which denotes unsustainable urbanisation through the intake of unsustainably sourced primary resources for the construction of buildings and infrastructure and the subsequent ever-increasing production of waste (Bucci Ancapi et al 2022a) (2022b) identified different policy instruments discussed for CBE implementation. To date, most instruments are linked to the adoption of material recycling and reuse, leaving urban aspects of a CBE, such as ecological regeneration and urban adaptation, insufficiently covered.…”
Section: Introductionmentioning
confidence: 99%